Tumor-infiltrating macrophages correlate with adverse prognosis and Epstein-Barr virus status in classical Hodgkin’s lymphoma - Peter Kamper; Knud Bendix; Stephen Hamilton-Dutoit; Bent Honoré; Jens R. Nyengaard; Francesco d’Amore (Haematologica, 2011)
Background Classical Hodgkin’s lymphoma is characterized by a minority of neoplastic cells surrounded by a heterogeneous background population of non-neoplastic cells including lymphoma-associated macrophages. High levels of expression of both the monocyte/macrophage lineage-associated antigens CD68 and CD163 have been suggested to have pro-tumor effects. The aim of our study was to correlate expression of CD68 and CD163 with the clinico-pathological features and prognosis of a cohort of patients with previously untreated Hodgkin’s lymphoma.Design and Methods A tissue microarray was constructed from paraffin-embedded tumor tissues from 288 cases of classical Hodgkin’s lymphoma. CD68 and CD163 expression was assessed immunohistochemically and the degree of macrophage infiltration within the tumor was scored using point grid counting. Clinical data were obtained from clinical records.Results The patients’ median age was 37 years (range, 6–86 years). The male to female ratio was 1.2. In classical Hodgkin’s lymphoma (n = 288) high CD68 and CD163 expression correlated, at the univariate level, with poorer overall survival (P=0.002 and P=0.03, respectively) and event-free survival (P=0.03 and P=0.04, respectively). At the multivariate level, high CD68 expression remained significantly predictive of overall survival (P=0.004). In addition, we demonstrated that both high CD68 and CD163 expression were associated with the presence of Epstein-Barr virus in the neoplastic cells (P=0.001 and P=0.0002, respectively).Conclusions In classical Hodgkin’s lymphoma, high expression of the macrophage/monocyte-related antigens CD68 and CD163 correlates with adverse outcome and with the presence of Epstein-Barr virus in the tumor cell population.